Characteristics of Teaching Material Development Based on Constructivism Learning Theory in Arabic Language Learning - Taufiq, Ahmad; Arrum Wijaya; Ahmad Ubaedi Fathuddin; Mujeeb Khan Saqafi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
The development of teaching materials is one of the key factors in improving the quality of education including Arabic language learning. Constructivism theory emphasizes active learning which learners construct their own knowledge through interaction with the environment and meaningful learning experiences. This article examined the principles of constructivism-based Arabic teaching materials development and its implementation in the context of education in Indonesia. This research employed a descriptive qualitative approach with the literature study method to examine in depth the characteristics of Arabic teaching material development based on constructivist theory through the stages of source identification, data collection, analysis, synthesis, and critique of relevant written sources. The results showed that constructivism-based teaching materials should include meaningful learning activities, contextual learning, collaboration, interaction, reflection, and feedback. The conclusion of this paper was that the development of Arabic teaching materials based on constructivism theory can contribute significantly to improving the quality of education. Teaching materials based on constructivism theory have the advantage of being able to make students active in learning activities and better understand the subject matter. However, constructivism teaching materials also have disadvantages such as requiring longer time and adequate teacher competence to guide students.